Genes coding for enterotoxins and verotoxins in porcine Escherichia coli strains belonging to different O:K:H serotypes: relationship with toxic phenotypes. - Blanco, M (1997)
Seventy-four E. coli strains isolated from piglets with diarrhea or edema disease in Spain were serotyped and examined for production of heat-labile (LT) and heat-stable (ST) enterotoxins (LT-I, LT-II, STaH, STaP, and STb) and verotoxins (VT1, VT2, and VT2v = VTe) by phenotypic (Vero cell assay and infant mouse test) and genotypic (colony hybridization and PCR) methods. In general, an excellent correlation was found between the results obtained with a PCR approach and those determined with biological assays. DNA probes used in the hybridization also showed a very good agreement with phenotypic results, with the exception of a VT1 probe that initially produced 10 false-positive reactions. The gene coding for STb (58 strains) was the most prevalent gene detected by PCR, followed by those coding for STa (46 strains), LT (19 strains), VT2v (11 strains), and VT1 (1 strain). Apparently, in Spain three seropathotypes are predominant: (i) O149:K91:H10 K88+ LT-I+ STb+, (ii) O141:K85ab:H- P987+ STaP+, and (iii) O138:K81:H14 or H- STaP+ VT2v+. We conclude that PCR is a fast, specific, and practical method for the identification of enterotoxin and VT genes in clinical and epidemiological studies.